Real men keep their word: tales from Kabul, Afghanistan - Loewen, Arley (Oxford University Press, 2005)
Providing a translation of Akram Osman's collection of Dari short stories, this title helps us understand traditional Kabul culture, and Kabul itself. These stories tell us about Afghan heroism and make us laugh at the pretensions of those who clamour for name and fame. It is for academic interested in modern Afghan studies, and general readers